Community Forestry As A Tool For Sustainable Forest Management And Rural Poverty Reduction In Cambodia - Ty , Sopkhun (2012)
As rural poverty persists, and deforestation and forest degradation continue, the trend of managing the forest has advanced from centralized or state managed to decentralized and community-based management. Innovative approaches, such as community forestry (CF), play an important role in supporting livelihood and the sustainable forest management. Community Forestry (CF) was launched in Cambodia to address the growing poverty in the rural areas. This study is aimed at investigating the performance of community forestry in alleviating poverty among the CF members in Cambodia. It seeks to evaluate the conditions of the implementation of community forestry in Cambodia and the effect of the factors in its implementation.